Preparation method and application of flexible graphite

By using potassium permanganate oxidation and phosphate ionic liquid intercalation agent in the preparation process of flexible graphite, combined with ultrasonic assist and impregnation liquid immersion steps, the problems of environmental pollution and safety hazards in the prior art are solved, and flexible graphite with excellent performance is prepared.

CN119612507AActive Publication Date: 2025-03-14BINZHOU DOUBLE PEAKS GRAPHITE SEALING MATERIAL
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411559233.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-14
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing flexible graphite preparation methods have problems of environmental pollution and safety hazards, especially acidic wastewater generated by using a large number of acidic reagents pollute the environment, and require high-temperature expansion processes to have safety hazards.

Method used

Potassium permanganate is used as the oxidizing agent to oxidize the graphite, and a mixed solution of phosphoric acid and ionic liquid is used as the intercalation agent. Through ultrasonic assisted dropwise addition and immersion liquid soaking steps, flexible graphite with excellent tensile strength and oxidation resistance is prepared.

Benefits of technology

The high tensile strength, good high temperature resistance, compression and rebound of flexible graphite are achieved, while avoiding safety hazards in acidic wastewater pollution and high temperature expansion processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117429220000081
    Figure BDA0005117429220000081
Patent Text Reader

Abstract

The invention belongs to the technical field of graphite materials, and particularly relates to a preparation method and application of flexible graphite, and the preparation method of the flexible graphite comprises the following steps: S1, adding graphite and potassium permanganate into a reaction container at room temperature, dropwise adding a mixed solution of phosphoric acid and an ionic liquid while performing ultrasonic treatment at the ultrasonic power of 130-140W and the ultrasonic temperature of 30-40 DEG C for 1-2 hours; continuously carrying out ultrasonic treatment for 2-3 hours after dropwise adding, washing to be neutral, and drying to obtain expandable graphite; s2, adding the expansible graphite obtained in the step S1 into an impregnation liquid, soaking for 15-20 minutes, filtering, and drying to obtain modified expansible graphite; and S3, expanding the modified expandable graphite obtained in the step S2 at 920-960 DEG C to obtain graphite worms, cooling the graphite worms, and pressing the cooled graphite worms at 85-95 DEG C and 19-21 MPa for 130-170 seconds to obtain the flexible graphite. The flexible graphite prepared by the preparation method of the flexible graphite is good in expansibility, excellent in compressibility, rebound resilience and high temperature resistance and good in tensile strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphite materials, and in particular relates to a preparation method and application of flexible graphite. Background Art

[0002] Carbon is an element that forms the skeleton of biological organisms. It mainly exists in the atmosphere, crust and organisms in the form of simple substances or compounds. Traditional carbon materials include charcoal, activated carbon, natural graphite, etc. With the development of science and technology, new carbon materials such as diamond, porous carbon, flexible graphite, etc. have gradually become the focus of research and development in the field of carbon materials. Flexible graphite is a material with excellent compressibility, resilience, sealing, softness and plasticity obtained by chemical treatment and high-temperature expansion using the layered structure of natural graphite. It can be used to prepare sealing materials, battery materials, flame retardant materials, etc., and has broad application prospects.

[0003] Patent CN102963884A discloses a method for preparing enhanced flexible graphite, using an oxidant KMnO 4 , H 2 O 2 , KClO 3 Compounding and sulfur-free intercalant HNO 3 The composite oxidation process produces a sulfur-free expandable graphite with an expansion ratio of more than 250ml / g. The expandable graphite particle size is reasonably proportioned and the staged pressing process is adopted to exhaust the air from the material more thoroughly, make the pressing more compact, and remove the air in the material, making the pressing tighter. The tensile strength of the sulfur-free flexible graphite can reach more than 5.3MPa, with good corrosion resistance and long service life. It can be used as a high-grade sealing material. The invention uses nitric acid as an intercalation agent, which will produce a large amount of acidic waste liquid and pollute the environment.

[0004] Patent CN108545737A discloses a method for preparing flexible graphite without high-temperature expansion, comprising the following steps: (1) mixing flaky graphite with appropriate amounts of concentrated sulfuric acid and hydrogen peroxide in an environment of ≤10°C; (2) allowing the mixture obtained in (1) to stand at room temperature to obtain expanded graphite; (3) baking the obtained expanded graphite for desulfurization at high temperature, condensing the gas after baking, and recovering sulfuric acid; (4) pressing the desulfurized expanded graphite to obtain flexible graphite. This method reduces the high-temperature expansion process in the preparation of expanded graphite, can recover sulfuric acid, avoids environmental pollution caused by acid-containing wastewater treatment, and reduces costs, but the invention still requires a large amount of concentrated sulfuric acid, which poses a safety hazard in the production process and causes harm to operators.

[0005] Therefore, there is an urgent need to develop a method for preparing flexible graphite that is environmentally friendly and can reduce safety hazards. Summary of the invention

[0006] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a method for preparing flexible graphite, and the obtained flexible graphite has good tensile strength, excellent high temperature resistance, compressibility and resilience.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A first aspect of the present invention provides a method for preparing flexible graphite, comprising the following steps:

[0009] S1. Add graphite and potassium permanganate into a reaction container at room temperature, and dropwise add a mixed solution of 74-90wt% phosphoric acid aqueous solution and ionic liquid while ultrasonicating, with an ultrasonic power of 130-140W and an ultrasonic temperature of 30-40°C. After the dropwise addition is completed, continue ultrasonicating for 2-3h, wash until neutral, and dry to obtain expandable graphite;

[0010] S2, adding the expandable graphite obtained in step S1 into the impregnation solution and soaking for 15-20 min, filtering, and drying to obtain modified expandable graphite;

[0011] S3, expanding the modified expandable graphite obtained in step S2 at 920-960° C. to obtain graphite worms, and after cooling the graphite worms, pressing at 85-95° C. and 19-21 MPa for 130-170 s to obtain flexible graphite.

[0012] Preferably, in step S1, the mass ratio of graphite to potassium permanganate is 1:(0.1-0.2), the dropping speed is 1-2 ml / s; the expansion volume of the expandable graphite is 425-440 ml / g; and the length of the graphite worms is 30-35 mm.

[0013] The present invention firstly uses potassium permanganate as an oxidant to oxidize graphite, and then adds a mixed solution of phosphoric acid and ionic liquid as an intercalation agent, thereby solving the problem that a large amount of acidic wastewater pollutes the environment by only using a large amount of acidic reagents such as sulfuric acid and nitric acid as intercalation agents in the traditional method. In addition, by soaking the obtained expandable graphite in an impregnation solution, the obtained flexible graphite has excellent tensile strength and oxidation resistance.

[0014] In some embodiments, the mass ratio of the 74-90 wt % phosphoric acid aqueous solution to the ionic liquid in step S1 is (1.8-2):1.

[0015] The present invention limits the mass ratio of phosphoric acid and ionic liquid so that the two can more easily enter the interlayer of graphite. In addition, the molecular structure of 2-methylacetanilide-citric acid ionic liquid is relatively large, which can improve the intercalation effect.

[0016] In some embodiments, the ratio of expandable graphite to impregnation liquid in step S2 is 1 g: (0.8-1) L.

[0017] The invention limits the ratio of expandable graphite to impregnating liquid so that the impregnating liquid can enter the interlayers of the expandable graphite, and at the same time avoids excessive accumulation of the impregnating liquid between the layers to reduce the compressibility and resilience of the flexible graphite.

[0018] In some embodiments, the method for preparing the ionic liquid comprises the following steps: dissolving 2-methylacetanilide and citric acid in ethanol, stirring at 40-50° C. for 11-13 hours, and drying to obtain the ionic liquid.

[0019] In some embodiments, the mass ratio of 2-methylacetanilide to citric acid is 1:(1.3-1.5).

[0020] The present invention limits the mass ratio of 2-methylacetanilide and citric acid by sour and The 2-methylacetanilide-citric acid ionic liquid is prepared by the neutralization reaction between the bases. The obtained ionic liquid contains amino and carboxyl groups with similar polarity to the oxidized graphite. Under the action of ultrasound, the interlayer force of the graphite is weakened, making it easier for the intercalant to enter the interlayer. The prepared expandable graphite has a larger expansion volume and increases the tensile strength of the flexible graphite.

[0021] In some embodiments, the impregnation solution, calculated as 100% by mass, includes the following raw materials: 2-4% phosphoric acid, 2-3% modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid, 0.5-1% boric acid, 6-8% metal ion liquid, and the balance is water.

[0022] In some embodiments, the preparation method of the modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid comprises the following steps: adding polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid, 3-amino-3-methylbutyric acid, and tetraisotitanate to dichloromethane, reacting at 70-80° C. for 5-6 hours, and rotary evaporating to obtain the modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid.

[0023] Preferably, the mass ratio of polyethylene glycol-catechol phenylboronic acid ester-polyglutamic acid to 3-amino-3-methylbutyric acid is 1:(0.2-0.3).

[0024] The present invention utilizes 3-amino-3-methylbutyric acid to modify polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid so that it can react with an intercalating agent and can evenly form an oxygen-isolating protective film on the surface and inside of the flexible graphite, thereby further improving its antioxidant property.

[0025] In some embodiments, the method for preparing the metal ionic liquid comprises the following steps:

[0026] (1) Add 1-hydroxyethyl-3-methylimidazolium chloride and diethylphosphoacetic acid to dichloromethane, add concentrated sulfuric acid while stirring, react at 70-80° C. for 5-6 hours, and rotary evaporate to obtain a compound;

[0027] (2) Add ferric chloride to the compound obtained in step (1), stir at 75-85° C. for 36-38 hours, and extract to obtain a metal ion liquid.

[0028] Preferably, the mass ratio of 1-hydroxyethyl-3-methylimidazolium chloride to diethylphosphoacetic acid is 1:(1.2-1.4).

[0029] The invention grafts 1-hydroxyethyl-3-methylimidazolium chloride with diethylphosphoacetic acid, and then reacts with ferric chloride to obtain an iron-containing metal ion liquid. The metal ion liquid is added into an impregnation liquid so that the impregnation liquid can be evenly distributed on the graphite surface, and the impregnated graphite still has good high temperature resistance after calcination. This may be because the cation grafting of the metal ion liquid contains a plurality of phosphorus groups, and the nitrogen atoms of the imidazole group and the iron ions can interact with the intercalation agent, so that the phosphorus atoms can effectively remain inside the expandable graphite, and the phosphorus and oxygen are cross-linked under the action of high temperature, so that the high temperature resistance of the flexible graphite can be increased. In addition, the presence of the iron atoms further increases the conductivity of the flexible graphite.

[0030] In some embodiments, the mass ratio of the compound to ferric chloride in step (2) is 1:(0.5-0.6).

[0031] The present invention limits the mass ratio of the compound to ferric chloride so that the Cl in the compound - It can fully react with ferric chloride to generate [FeCl 4 ] - , increasing conductivity and the coordination effect of iron ions increase the tensile strength of flexible graphite.

[0032] A second aspect of the present invention provides an application of flexible graphite in a flexible graphite bipolar plate.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The present invention firstly oxidizes graphite with potassium permanganate as an oxidant, and then adds a mixed solution of phosphoric acid and ionic liquid as an intercalation agent, thereby solving the problem that a large amount of acidic wastewater pollutes the environment by only using a large amount of acidic reagents such as sulfuric acid and nitric acid as intercalation agents in the traditional method. In addition, by soaking the obtained expandable graphite in an impregnation solution, the obtained flexible graphite has excellent tensile strength and oxidation resistance.

[0035] 2. The present invention prepares 2-methylacetanilide and citric acid in a specific mass ratio by sour and The ionic liquid 2-methylacetanilide-citric acid is prepared by a neutralization reaction between alkalis. The obtained ionic liquid contains amino and carboxyl groups with similar polarity to the oxidized graphite. Under the action of ultrasonic assistance, the interlayer force of the graphite is weakened, making it easier for the intercalant to enter the interlayer. The prepared expandable graphite has a larger expansion volume and increased tensile strength.

[0036] 3. The present invention grafts 1-hydroxyethyl-3-methylimidazolium chloride with diethylphosphoacetic acid, and then reacts with ferric chloride to obtain an iron-containing metal ion liquid, which can be evenly distributed on the graphite surface, so that the graphite after impregnation and calcination has good high temperature resistance. This may be because the cation grafting of the metal ion liquid contains multiple phosphorus groups, and the nitrogen atoms of the imidazole group and the iron ions in the anions can interact with the intercalation agent, so that the phosphorus atoms can effectively remain inside the expandable graphite. Under the action of high temperature, phosphorus and oxygen are cross-linked with each other, which can increase the high temperature resistance of the flexible graphite. In addition, the presence of iron ions further increases the conductivity of the flexible graphite. DETAILED DESCRIPTION

[0037] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following examples and comparative examples are only used to illustrate the present invention and are not intended to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0038] In order to facilitate those skilled in the art to implement the present invention, some raw materials and manufacturers of the embodiments and comparative examples are described as follows:

[0039] The compounds and related reagents used in the following examples and comparative examples can all be purchased from the market, among which polyethylene glycol-catechol phenylboronic acid-polyglutamic acid was purchased from Xi'an Qiyue Biotechnology Co., Ltd., with Mn=600; natural flake graphite was purchased from Qingdao Mingrun Chenyue Graphite Co., Ltd., with a particle size of 50 mesh.

[0040] Preparation Example 1

[0041] The preparation method of ionic liquid-1 comprises the following steps: dissolving 10 g of 2-methylacetanilide and 14 g of citric acid in 100 ml of anhydrous ethanol, stirring at 45° C. for 12 h, and drying to obtain ionic liquid-1.

[0042] Preparation Example 2

[0043] The preparation method of ionic liquid-2 is the same as that of Preparation Example 1, except that the amount of citric acid added is 11 g.

[0044] Preparation Example 3

[0045] The preparation method of modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid comprises the following steps: adding 10g polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid, 2.4g 3-amino-3-methylbutyric acid, and 0.01g tetraisotitanate into 500ml dichloromethane, reacting at 75°C for 5.5h, and rotary evaporating to obtain the modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid.

[0046] Preparation Example 4

[0047] The preparation method of metal ion liquid-1 comprises the following steps:

[0048] (1) Add 10 g of 1-hydroxyethyl-3-methylimidazolium chloride and 13 g of diethylphosphoacetic acid to 100 ml of dichloromethane, add 1 ml of 95 wt% concentrated sulfuric acid while stirring, react at 75° C. for 5.5 h, and evaporate by rotary evaporation to obtain a compound;

[0049] (2) Add 5.5 g of ferric chloride to 10 g of the compound obtained in step (1), stir at 80° C. for 37 h, and extract to obtain metal ionic liquid-1.

[0050] Preparation Example 5

[0051] The preparation method of metal ionic liquid-2 is the same as that of Preparation Example 4, except that the amount of ferric chloride added is 4.5 g.

[0052] Example 1

[0053] A method for preparing flexible graphite comprises the following steps:

[0054] S1. Add 10g natural flake graphite and 1.5g potassium permanganate into a reaction container at room temperature, and drop 40ml of a mixed solution of 75wt% phosphoric acid aqueous solution and ionic liquid-1 while ultrasonicating, the mass ratio of 75wt% phosphoric acid aqueous solution to ionic liquid-1 is 1.9:1, the dropping speed is 1ml / s, the ultrasonic power is 135W, the ultrasonic temperature is 35°C, and after the dropwise addition is completed, continue ultrasonicating for 2.5h, wash until neutral, and dry to obtain expandable graphite;

[0055] S2, adding 10g of the expandable graphite obtained in step S1 into 8L of impregnation solution and soaking for 18min, filtering, and drying to obtain modified expandable graphite;

[0056] S3, expanding 8 g of the modified expandable graphite obtained in step S2 at 940° C. to obtain graphite worms, and then cooling the graphite worms and pressing them at 90° C. and 20 MPa for 150 s to obtain flexible graphite;

[0057] The impregnation solution, calculated by mass percentage of 100%, includes the following raw materials: 75wt% phosphoric acid, 3%, modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid, 2.5%, boric acid, 0.8%, metal ion liquid-1, 7%, and water, 86.7%.

[0058] Example 2

[0059] A method for preparing flexible graphite comprises the following steps:

[0060] S1. Add 10g natural flake graphite and 1.5g potassium permanganate into a reaction container at room temperature, and drop 40ml of a mixed solution of 75wt% phosphoric acid aqueous solution and ionic liquid-1 while ultrasonicating, the mass ratio of 75wt% phosphoric acid aqueous solution to ionic liquid-1 is 1.9:1, the dropping speed is 1ml / s, the ultrasonic power is 130W, the ultrasonic temperature is 30°C, and after the dropwise addition is completed, continue ultrasonicating for 2h, wash until neutral, and dry to obtain expandable graphite;

[0061] S2, adding 10g of the expandable graphite obtained in step S1 into 5L of impregnation solution and soaking for 15min, filtering, and drying to obtain modified expandable graphite;

[0062] S3, expand 8g of the modified expandable graphite obtained in step S2 at 920°C to obtain graphite worms, cool the graphite worms and press them at 85°C and 21MPa for 130s to obtain flexible graphite. ;

[0063] The impregnation solution, calculated by mass percentage of 100%, includes the following raw materials: 75wt% phosphoric acid 2%, modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid 2%, boric acid 0.5%, metal ion liquid-1 6%, and water 89.5%.

[0064] Example 3

[0065] A method for preparing flexible graphite comprises the following steps:

[0066] S1. Add 10g natural flake graphite and 1.5g potassium permanganate into a reaction container at room temperature, and drop 40ml of a mixed solution of 75wt% phosphoric acid aqueous solution and ionic liquid-1 while ultrasonicating, the mass ratio of 75wt% phosphoric acid aqueous solution to ionic liquid-1 is 1.9:1, the dropping speed is 1ml / s, the ultrasonic power is 140W, the ultrasonic temperature is 40°C, and after the dropwise addition is completed, continue ultrasonicating for 3h, wash until neutral, and dry to obtain expandable graphite;

[0067] S2, adding 10g of the expandable graphite obtained in step S1 into 10L of impregnation solution and soaking for 20min, filtering, and drying to obtain modified expandable graphite;

[0068] S3, expanding 8 g of the modified expandable graphite obtained in step S2 at 960° C. to obtain graphite worms, and then cooling the graphite worms and pressing them at 95° C. and 19 MPa for 170 s to obtain flexible graphite;

[0069] The impregnation solution, calculated by mass percentage of 100%, includes the following raw materials: 75wt% phosphoric acid 4%, modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid 3%, boric acid 1%, metal ion liquid-1 8%, and water 84%.

[0070] Example 4

[0071] A method for preparing flexible graphite, the specific implementation method is the same as that of Example 1, except that an equal amount of ionic liquid-1 is replaced by ionic liquid-2.

[0072] Example 5

[0073] A flexible graphite and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of metal ion liquid-1 is replaced by metal ion liquid-2.

[0074] Example 6

[0075] A flexible graphite and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the amount of impregnation liquid added is 7L.

[0076] Example 7

[0077] A flexible graphite and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that an equal amount of modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid is replaced by polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid.

[0078] Comparative Example 1

[0079] A method for preparing flexible graphite comprises the following steps:

[0080] S1. Add 10g natural flake graphite and 1.5g potassium permanganate into a reaction vessel at room temperature, and add 40ml 75wt% phosphoric acid aqueous solution dropwise while ultrasonicating, with a dropping speed of 1ml / s, an ultrasonic power of 135W, and an ultrasonic temperature of 35°C. After the dropping is completed, continue ultrasonicating for 2.5h, wash until neutral, and dry to obtain expandable graphite;

[0081] S2, expanding 8 g of the modified expandable graphite obtained in step S1 at 940° C. to obtain graphite worms, cooling the graphite worms and pressing them at 5.5 MPa for 7 min, then heating them to 90° C. and pressing them for 150 s to obtain flexible graphite;

[0082] Performance Testing

[0083] The flexible graphite obtained in each example and comparative example was pressed into a 0.5 mm flexible graphite plate and subjected to the following tests.

[0084] 1. Compression rate and rebound rate

[0085] The compression rate and the resilience rate of the flexible graphite sheets obtained in various embodiments and comparative examples were tested according to JBT / 9141.4-2013.

[0086] 2. Tensile strength

[0087] The tensile strength of the flexible graphite sheets obtained in various embodiments and comparative examples was tested according to JBT / 9141.2-2013.

[0088] 3. High temperature resistance

[0089] The thermal weight loss rate of the flexible graphite obtained in each embodiment and comparative example at 670° C. was tested according to JBT / 9141.7-2013.

[0090] The test results are shown in Table 1.

[0091] Table 1

[0092]

[0093] By comparing the experimental data of Examples 1-3 in Table 1, it can be seen that the flexible graphite obtained by the preparation method of the flexible graphite has greater tensile strength, good high temperature resistance, compressibility and resilience; compared with Example 1, Example 4 shows that the ratio of 2-methylacetanilide and citric acid in the ionic liquid is changed, which may lead to a decrease in the purity of the ionic liquid, a weakening of the intercalation effect, and a decrease in the resilience, compressibility and high temperature resistance; compared with Example 1, Example 5 shows that the ratio of the compound to ferric chloride in the metal ionic liquid is changed, which may lead to a decrease in the coordination effect. The tensile strength of the flexible graphite is weak; compared with Example 1, it can be seen that the change in the ratio of expandable graphite to the impregnating liquid may lead to a decrease in the amount of impregnating liquid entering the flexible graphite interlayer, resulting in a decrease in the high temperature resistance of the flexible graphite; compared with Example 1, it can be seen that the use of unmodified polyethylene glycol-catechol phenylboronic acid ester-polyglutamic acid may lead to uneven distribution of the impregnating liquid between the layers, resulting in a decrease in the high temperature resistance of the flexible graphite; compared with Example 1 and Comparative Example 1, it can be seen that the various properties of the flexible graphite obtained using the conventional preparation method are all reduced.

[0094] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing flexible graphite, characterized in that: The following steps are involved: S1. Add graphite and potassium permanganate into a reaction container at room temperature, and dropwise add a mixed solution of 74-90wt% phosphoric acid aqueous solution and ionic liquid while ultrasonicating, with an ultrasonic power of 130-140W and an ultrasonic temperature of 30-40°C. After the dropwise addition is completed, continue ultrasonicating for 2-3h, wash until neutral, and dry to obtain expandable graphite; S2, adding the expandable graphite obtained in step S1 into the impregnation solution and soaking for 15-20 min, filtering, and drying to obtain modified expandable graphite; S3, expanding the modified expandable graphite obtained in step S2 at 920-960° C. to obtain graphite worms, and after cooling the graphite worms, pressing at 85-95° C. and 19-21 MPa for 130-170 s to obtain flexible graphite.

2. The method for preparing flexible graphite according to claim 1, characterized in that: In the step S1, the mass ratio of the 74-90 wt % phosphoric acid aqueous solution to the ionic liquid is (1.8-2):

1.

3. The method for preparing flexible graphite according to claim 1, characterized in that: In the step S2, the ratio of expandable graphite to impregnation liquid is 1 g: (0.8-1) L.

4. The method for preparing flexible graphite according to claim 1, characterized in that: The preparation method of the ionic liquid comprises the following steps: dissolving 2-methylacetanilide and citric acid in ethanol, stirring at 40-50° C. for 11-13 hours, and drying to obtain the ionic liquid.

5. The method for preparing flexible graphite according to claim 4, characterized in that: The mass ratio of the 2-methylacetanilide to the citric acid is 1:(1.3-1.5).

6. The method for preparing flexible graphite according to claim 1, characterized in that: The impregnation solution, calculated by mass percentage of 100%, includes the following raw materials: 2-4% phosphoric acid, 2-3% modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid, 0.5-1% boric acid, 6-8% metal ion liquid, and the balance is water.

7. The method for preparing flexible graphite according to claim 6, characterized in that: The preparation method of the modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid comprises the following steps: adding polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid, 3-amino-3-methylbutyric acid and tetraisotitanate into dichloromethane, reacting at 70-80° C. for 5-6 hours, and rotary evaporating to obtain the modified polyethylene glycol-phenylboronic acid catechol ester-polyglutamic acid.

8. The method for preparing flexible graphite according to claim 6, characterized in that: The preparation method of the metal ion liquid comprises the following steps: (1) Add 1-hydroxyethyl-3-methylimidazolium chloride and diethylphosphoacetic acid to dichloromethane, add concentrated sulfuric acid while stirring, react at 70-80° C. for 5-6 hours, and rotary evaporate to obtain a compound; (2) Add ferric chloride to the compound obtained in step (1), stir at 75-85° C. for 36-38 hours, and extract to obtain a metal ion liquid.

9. The method for preparing flexible graphite according to claim 8, characterized in that: The mass ratio of the compound to ferric chloride in step (2) is 1:(0.5-0.6).

10. Use of the flexible graphite obtained by the method for preparing the flexible graphite according to any one of claims 1 to 9 in a flexible graphite bipolar plate.

Citation Information

Patent Citations

  • Preparation method of reinforced flexible graphite

    CN102963884A

  • Preparation method of flexible graphite without high-temperature expansion

    CN108545737A

  • Preparation of low temperature expandable graphite

    CN101327926A

  • Manufacturing method for high temperature-resistant high-strength flexible graphite material

    CN102897754A

  • Graphene preparation method

    CN103626163A